Stressors experienced in elite sport by physiotherapists - Kerai, S.; Wadey, R.; Salim, J. (Sport, Exercise, and Performance Psychology, 2019)
This study extends stress research by exploring the stressors experienced by physiotherapists working in elite sport. The physiotherapists who were interviewed have prepared athletes and worked with them at international events (e.g., Olympic and Paralympic Games). Transcripts were analyzed using thematic analysis. Methodological rigor and generalizability were maximized through self-reflexivity and eliciting external reflections before seeking publication. Five themes were identified: I Am Not a Machine, This Is Sport, Relationships Are Messy, Under the Microscope, and Beyond One`s Remit. These themes illustrate that sports physiotherapists experience a wide variety of stressors (e.g., workload, power relationships, and moral and ethical conflicts), with diverse consequences (e.g., work-life conflict, job insecurity, and relationship breakdown). Although these findings resonate with practitioners in other sport science and management roles, they also provide unique insights into this population. Practical implications are discussed across multiple levels (i.e., policy, cultural, organizational, interpersonal, and intrapersonal).